The utility of WHO-five-well-being index as a screening tool for depression among elderly - R., Pracheth (International Journal Of Community Medicine And Public Health, 2017)
Background:WHO-Five-Well-being Index (WHO-5) is an uncomplicated questionnaire used to appraise subjective well-being. This study was conducted to determine the validity and internal consistency of WHO-5 in the appraisal of depression among elderly and establish the agreement between GDS-15 and WHO-5. Methods:After obtaining clearance from the institutional ethics committee, a cross-sectional study was conducted for 6 months in an urban slum on elderly persons aged ≥60 years, with consent. A pre-designed and semi-structured interview schedule was used to collect the information. WHO-5 was used to assess depression. It was translated to local language and then back translated. To confirm the diagnosis of major depression, Mini International Neuropsychiatric Interview (MINI) was adopted. The relationship between WHO-5 mean scores and the grading of depression as per Geriatric Depression Scale Short Form (GDS-15) was determined. Results:A total of 218 study participants were included, of which 44 (20.18%) were depressed. Mean raw WHO-5 score was 14.80 ± 5.14. WHO-5 demonstrated a good internal consistency (Cronbach’s Alpha=0.85). The concurrent validity while considering MINI was gold standard was good. Those found to be normal when subjected to MINI had a significantly lower score (15.28 ± 5.2) when compared to those diagnosed as depressed (7.46 ± 4.31) [t=8.728, df=218, p<0.0001]. When convergent validity was assessed, a good correlation was found between GDS-15 and WHO-5 (r=0.68, p<0.0001). Conclusions:WHO-5 is a valid and reliable tool to assess depression among elderly. The elderly who present to health centres may be subjected to screening of depression and well-being, using WHO-5.